1987
DOI: 10.1007/bf02578009
|View full text |Cite
|
Sign up to set email alerts
|

Angioplasty-related iliac artery rupture: Treatment by temporary balloon occlusion

Abstract: A case of nonsurgical treatment of common iliac artery rupture secondary to percutaneous transluminal angioplasty is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In 1991, Milford et al reported the first case of successful hemostasis achieved solely unitizing subclavian artery balloon occlusion [ 10 ]. A 1987 report describes balloon occlusion to control iliac arterial bleeding without any subsequent open surgical intervention [ 11 ]. Milford et al describe a case in which a 7-French PTA catheter with a 10-mm balloon 4 cm in length was placed distal to the vertebral origin, while overlapping with the catheter's entry site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1991, Milford et al reported the first case of successful hemostasis achieved solely unitizing subclavian artery balloon occlusion [ 10 ]. A 1987 report describes balloon occlusion to control iliac arterial bleeding without any subsequent open surgical intervention [ 11 ]. Milford et al describe a case in which a 7-French PTA catheter with a 10-mm balloon 4 cm in length was placed distal to the vertebral origin, while overlapping with the catheter's entry site.…”
Section: Discussionmentioning
confidence: 99%
“…To our understanding, only one other case documents the use of a balloon shorter than the vessel diameter. In fact, the balloon used in this case was 6-mm and was used to repair an iatrogenic external iliac artery rupture during a percutaneous transluminal angioplasty [ 6 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…60 The timing of inflation is variable, with the average time varying from 5 to 30 minutes. [61][62][63][64] Tamponade with a slightly larger balloon may be helpful when the initial tamponade is unsuccessful (►Fig. 8) but results are unpredictable.…”
Section: Arterial Rupturementioning
confidence: 99%
“…Temporary balloon occlusion has been used in the setting of arterial trauma [3,4] and in the repair of leaking abdominal aortic aneurysms [5]. For injuries to the brachiocephalic artery, this technique permits easier, less invasive operative dissection and may eliminate the need for clamping the artery proximal to the injury.…”
mentioning
confidence: 99%